2007
DOI: 10.3141/1994-14
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Park-and-Ride Services in a Multimodal Transport Network with Elastic Demand

Abstract: With the rapid development of metro systems in large Asian cities, such as Hong Kong and Shanghai, China, local authorities are developing park-and-ride (P&R) schemes to encourage commuters to reach the cities’ central areas by transferring from private cars to metro at stations with P&R facilities. A network equilibrium formulation can be used to model P&R services in a multimodal transportation network with elastic demand. It is assumed that commuters can complete their journeys by three options:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…The positive sides of Park & Ride system are noticed also by Li et al, [15] claiming that P&R schemes have been widely recognized as an effective means of addressing traffic congestion problems in densely developed urban areas. These schemes are used as a tool to encourage commuters to undertake their journeys in two parts: first driving a private car to a car park near transit stations and then completing the remainder of the journey by taking a transit mode.…”
Section: Park and Ridementioning
confidence: 81%
“…The positive sides of Park & Ride system are noticed also by Li et al, [15] claiming that P&R schemes have been widely recognized as an effective means of addressing traffic congestion problems in densely developed urban areas. These schemes are used as a tool to encourage commuters to undertake their journeys in two parts: first driving a private car to a car park near transit stations and then completing the remainder of the journey by taking a transit mode.…”
Section: Park and Ridementioning
confidence: 81%
“…Concerning the existence and uniqueness of the VI Eq. (A.1) solution, relevant discussions are the same with those about the fixed point, so omitted here (Fisk, Boyce 1983;Li et al 2007b). Nagurney (2010a) showed that VI problems have unique solutions when some monotonic conditions are satisfied.…”
Section: Appendixmentioning
confidence: 99%
“…Concerning the existence and uniqueness of the VI equation solution, relevant discussions are the same with those about the fixed point, so omitted here. 61,62 Charnes et al 63 showed that VI problems have unique solutions when some monotonic conditions are satisfied.…”
Section: Conclusion and Further Studiesmentioning
confidence: 99%